Analisis Sistem Distribusi Pupuk Bersubsidi di Kabupaten Simalungun, Sumatera Utara (Studi Kasus CV. Mas Ayu Lestari) - GAOL, BHAKTI A. LUMBAN; ANGGRENI, I GUSTI AYU AGUNG LIES; ARISENA, GEDE MEKSE KORRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p05, 2023)
Analysis of Subsidized Fertilizer Distribution System in Simalungun Regency, North Sumatra (Study Case: Cv. Mas Ayu Lestari ) To increase production and productivity, fertilizer is one of the main keys to success in farming systems. Subsidized fertilizers are fertilizers whose procurement and distribution receive subsidies from the government for the needs of farmers. The scarcity of subsidized fertilizers occurs due to uncertain causes, such as delays in distribution or missing somewhere, while farmers must pay attention to the planting period. The purpose of this study was to identify subsidized fertilizer distribution system and identifying subsidized fertilizer distribution problems in Simalungun Regency, North Sumatra. The research method used is qualitative with the type of case study. Sources of data obtained are primary data and secondary data. The results of the study concluded that there were still problems with the distribution system of subsidized fertilizers in Simalungun Regency, North Sumatra which resulted in not achieving the right 6 principles, especially in the right place, in the right amount and at the right time. The suggestions that can be submitted are to pay more attention to the management of the availability of subsidized fertilizers among farmers through supervision and communication among actors in distributing subsidized fertilizers.